Intervención fisioterapéutica en paciente femenino de 13 años con fractura de peroné en la extremidad izquierda que acude a la Federación Deportiva de Los Ríos área de fisiatría - Meléndez Yánez, Nayeli Michelle (2025)
At the Los Ríos Sports Federation, a personalized physiotherapy intervention plan has been designed for a 13-year-old patient with a non-displaced fibula fracture in the left limb, a condition caused by a traumatic factor. It focuses on thoroughly evaluating the biomechanics of the ankle and its gait to better understand how these conditions affect its movement and function. Assessments and tests definitively reveal muscle imbalances and restricted mobility secondary to the swelled condition and painful symptoms; therefore, the examination develops a treatment protocol concentrating on muscle-strengthening and lengthening exercises for the musculature of the lower extremity on the left side. These exercises will be carried out progressively and monitored to ensure the maximum stability of the left lower limb through increased strength and flexibility. Finally, manual therapy techniques shall be administered, massage, and manipulation techniques used to mobilize the ankle joint to eliminate stiffness and enhance the circulation of blood in the affected area.. These techniques help relieve pain and stiffness, promoting the patient's recovery and physical well-being.